Indicators for Tracking the Global Goal on Adaptation: Insights from 50+ African Countries - Nowak, Andreea C.; Njuguna, Lucy; Zorrilla-Miras, Pedro; Sanz, María-José; López Gunn, Elena; Zafra-Calvo, Noelia; Wamukoya, George; Rosenstock, Todd S. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Key messages: